PROGRAM SANTRI FILANTROPI: PENDAMPINGAN PENGUATAN ASET PADA KOMUNITAS NU CARE-LAZISNU MWCNU KREJENGAN KABUPATEN PROBOLINGGO - Imam Syafi'i; M. Sulthon; Babur Rahman; Nanik Paripati Qomariyah; Siti Sholeha (As-Sidanah, 2024)
The phenomenon of growing philanthropy, especially in sub-districts, Krejengan, Probolinggo Regency is an interesting study and requires assistance to increase its assets and potential. The aim of implementing this service is to explore asset potential, find asset development strategies, ensure the continuity of the Santri Philanthropy program, and expand partnerships based on the results achieved in the NU Care-LAZISNU MWCNU Krejengan community, Probolinggo Regency. In its implementation, this assistance uses an Asset - Based Community Development approach. Where the steps of discovery, dream, design, define, and destiny are carried out. In the context of this service, based on strategic analysis and how the ABCD method works, the general description of the implementation of mentoring includes the preparation stage, implementation stage, and reporting stage. As a result of the mentoring, the Santri Philanthropy Program is a potential asset for the NU Care-LAZISNU community in developing the KOIN NU movement. The NU Coin movement has been formed since 2020, and residents are enthusiastic about taking part because the majority of local residents are Nahdiyin residents, and the results obtained will be felt to be more beneficial given the existing potential. The strategy for developing assets in the NU Care - LAZISNU community from the Santri Philanthropy program is: planning, organizing, methods, and supervision. And the results achieved include uniform and organized program Standard Operating Procedures (SOP), control and management, scheduled reporting, and scheduled and planned tasharruf activities.